Ultra-Capacitor Storage in Regenerative Braking (International Journal of Innovative Research in Engineering & Management, 2021)
The modern world today has a wide variety of energy sources  to integrate them, maximize, the efficiency of transmission  and increase the accessibility of electricity. Since the late  1800s, only steam and EV disappeared with the introduction  of the steam engine, ICE, and electric vehicles. However,  electricity became viable for car drives as technology  improved. Electric vehicles have recently become popular  with improved technology in the field of batteries and  electronics. At certain points, the energy consumption of  these electric vehicle’s peaks. For example, when the vehicle  stops at a stop, the increased starting torque requires a higher  motor power supply. This study identifies and analyses the  use for the energy demand of regenerative braking and ultra capacitors.
Keywords: Ultra- Capacitor; Voltage; Simulink; Braking; Converter